Pendampingan Remaja untuk Berhenti Merokok dengan Pendekatan Transtheoretical Model (Stages of Change) di Posyandu Remaja Desa Mliwis Boyolali - Tanjung Anitasari Indah Kusumaningrum; Ayu Khoirotul Umaroh; Dian Purworini; Siti Soekiswati; Arif Pristianto; Zulia Setiyaningrum; Nanda Hani Nur Pertiwi; Sabrina Cantika Putri Sandrana; Novyanti Setiyo Rini; Muhammad Irfan Zahran; Faturohit Rois Imron Santoso; Zavier Ferodova Al Fitroh; Pradhana Satria Pinandhita (Universitas Muhammadiyah Surakarta, 2024)
The partner for community service activities was the youth posyandu in Tambakboyo Hamlet, Mliwis. Adolescent boys at Mitra Posyandu have a smoking habit. There were 25% of teenage boys who have tried to stop smoking but failed. The problems faced by posyandu partners are the difficulty of generating teenagers' intention to stop smoking, teenagers also don't know how to stop smoking, and there are still many teenagers who relapse or smoke again even though they are already at the action stage. The aim of this program was to provide smoking cessation education and health messages with the stages of change in smoking behavior in each adolescent using a transtheoretical model approach and monitoring and strengthening smoking cessation by adolescent cadres. The methods used were socializing activities to youth posyandu, providing media on how to stop smoking, providing education regarding efforts to stop smoking, training youth cadres, designing applications for monitoring efforts to stop smoking, and assisting teenagers to stop smoking. The results of this service were that there was an increase in adolescent knowledge by 0.17% after being given smoking cessation education, the formation of peer counselors consisting of adolescent cadres, the existence of health media in the form of pocket books and booklets, and the creation of the Smoke Stop Step (3S) application to monitor efforts of quit smoking. After using the application and providing health messages according to the smoking cessation stages, there were 3 teenagers who started to intend to stop smoking and 1 teenager entered the preparatory stage (preparing to stop smoking).